Examining the association between cultural self-construal and dream structures in the United States and Japan - Konakawa, Hisae; Kawai, Toshio; Tanaka, Yasuhiro; Hatanaka, Chihiro; Bowen, Kimberly; Koh, Alethea (Frontiers in Psychology, 2023)
Cultural differences in self-construal, human relationships, and values between Western and East Asian people have been suggested. The aim of this article is to investigate cultural difference in dreamers’ self-construal based on their dreams. We examined the dreams sampled via online questionnaires from 300 non-clinical participants from America and Japan, respectively. The free response for the contents of “impressive dreams in childhood” “recent impressive dreams” was categorized into the five general dream structural patterns. Besides, the participants were asked to answer the scales to investigate participants’ cultural self-construal. The current results revealed the prevalence of the independent view of self in American participants and the interdependent view of self in Japanese participants. In addition, we found significant cultural differences in the dream length and structural patterns. For American dreams, the dream-ego had a clear will and strong mobility, and there were obvious ends of dream events. Conversely, for Japanese dreams, the weak agency and vague conscious of the dream-ego were shown, and others could play a main role in one’s dreams. These results suggested that each characteristic of the American and Japanese samples may be influenced by the differences in self-construal or in the process of self-formation between American and Japanese cultures.